Implementation of the PjBL learning model assisted by the TikTok application in the literary expression course - Hiasa, Fina; Agustina, Emi; Tawandorloh, Ku-Ares (BAHASTRA, 2022)
This study aims to improve the learning quality of the Literary Expression course using the TikTok application as a learning medium in the application of the PjBL model to the seventh semester students of the Indonesian Language Education Study Program FKIP Bengkulu University. The assignment of making this TikTok video is an implementation of the PjBL model where students not only perform analysis but also explore, collect information, interpret, and assess. This research was conducted in two cycles. The results of this study indicate that the use of the TikTok application as a learning medium in the application of the PjBL model can improve student learning outcomes. The achievement targets were obtained in cycle II with the following details: 15 students or 42% got category A, 17 students or 47% got category B, 4 students or 11% got category C, and none or 0 students got category D. The results of the response questionnaire showed a final score of 24 .61 or obtained an average of 4.1 which means that the category most chosen by students is agree. These results indicate that the implementation of the project assignment of making short stories expressing videos using the TikTok application is of interest to students. Not only reaching aspects of knowledge implementation but also increasing students' creativity and interest in learning activities.